Kinetics of organ response and survival following normalization of the serum free light chain ratio in AL amyloidosis. Issue 3 (16th January 2015) - Kaufman, Gregory P.; Dispenzieri, Angela; Gertz, Morie A.; Lacy, Martha Q.; Buadi, Francis K.; Hayman, Suzanne R.; Leung, Nelson; Dingli, David; Lust, John A.; Lin, Yi; Kapoor, Prashant; Go, Ronald S.; et al.
<x xml:space="preserve">Abstract</x> Despite successful treatment of the clonal plasma cell implicated in its pathogenesis, patients with AL amyloidosis (AL) experience significant morbidity related to underlying amyloid mediated organ dysfunction. While normalization of the serum free light chain measurements [normal ratio of involved and uninvolved free light chains (nFLCr)] is the goal of therapy and centerpiece of hematologic response criteria, achieving (or not achieving) meaningful organ response (OR) is clinically significant for its implications on long‐term symptomatology as well as overall survival (OS), and remains the ultimate goal of treatment. Expectations for organ recovery following successful therapy leading to nFLCr in AL remain poorly described. We evaluated the timeframe and predictive factors for OR, and long‐term outcome, in 313 AL patients who achieved nFLCr following therapy initiation. OR was seen in 80% of surviving AL patients within 1‐year of nFLCr. Patients achieving early OR within 1 year of nFLCr had superior OS compared with those who despite obtaining nFLCr did not achieve early OR. We further evaluated factors predicting OR and OS among patients achieving nFLCr. Higher values of dFLC (involved–uninvolved) at diagnosis predict OR, and early OR predicts improved OS following successful hematologic therapy in AL. Am. J. Hematol. 90:181–186, 2015. © 2014 Wiley Periodicals, Inc.